2014
DOI: 10.1007/s00464-014-3629-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation for Barrett’s-associated intramucosal carcinoma: a multi-center follow-up study

Abstract: RFA is an effective and durable treatment option for Barrett's-associated IMC. Greater than 80% of patients will achieve and maintain complete eradication of IMC at a mean of 2 years follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…This included 21 RFA studies that reported 603 cases of IM recurrence in 3186 patients over 5741 patient-years of follow-up. 9,12,14,15,18,21,22,27,29,30,32,39-41,43,47,49,51,53,54 Figure 1 shows the schematic diagram of study selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included 21 RFA studies that reported 603 cases of IM recurrence in 3186 patients over 5741 patient-years of follow-up. 9,12,14,15,18,21,22,27,29,30,32,39-41,43,47,49,51,53,54 Figure 1 shows the schematic diagram of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen of the 41 included studies were multicenter studies. 12,21,29,34,39,41,44,47,49-51,53,54 Mean patient age at endoscopic therapy was 61.4 years, and 78.9% were men. The median of average follow-up after CRIM was 2.5 years, ranging from 1 year to 10.5 years in individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the recurrence of dysplasia and neoplasia is reduced by the use of ablative therapy to eliminate residual intestinal metaplasia following induction of remission in IMC by EMR [7,32,33]. This approach has been shown to be comparable to that of esophagectomy in both subjects with HGD and IMC [7,34] The current recommendations from the American College of Gastroenterology (ACG), American Gastroenterological Association (AGA), American Society for M A N U S C R I P T…”
Section: Hgd Imcmentioning
confidence: 93%
“…Radiofrequency ablation (RFA), with or without endoscopic mucosal resection (EMR), is also recommended for select individuals with nondysplastic BE who are judged to be at increased risk for further neoplastic progression. 104, 106, 107 To complement the early detection and mucosal ablation/resection in management of patients with BE, a need exists for chemopreventive agents. Three classes of medications are potentially beneficial in reducing the cancer risk of BE: antacids, anti-inflammatory drugs, and antibiotics, of which antacids are the only medication routinely used in clinical practice in the treatment of reflux disorders.…”
Section: Potential Targets For Chemoprevention Of Esophageal Adenocarmentioning
confidence: 99%